Pengaruh Dukungan Organisasi, Spritualitas di Tempat Kerja Terhadap Kinerja Pegawai Melalui Komitmen Organisasi Sebagai Variabel Intervening (Studi Kasus Badan Kesatuan Bangsa dan Politik Provinsi Jambi) - Ardiansyah Ardiansyah; Edwar MS; Musnaini Musnaini (Universitas Batanghari Jambi, 2022)
This study aims to analyze the effect of organizational support and spirituality in the workplace through organizational commitment on employee performance. The target population for this research is Civil Servants (PNS) in the National Unity and Politics Agency of Jambi Province, totaling 89 people. Where the sampling technique in this study used the Krejcie and Morgan tables with a margin of error of 5% so that a sample of 76 people was obtained. This study uses a quantitative approach with survey methods and uses Partial Least Square (PLS) data analysis. The results showed that organizational support and spirituality in the workplace directly affect organizational commitment and employee performance. While indirectly only organizational support has an indirect effect through organizational commitment, while spirituality in the workplace does not have an indirect influence through organizational commitment as an intervening variable.